A case for scholarly activity in vocational education in Australia. Issue 1 (9th February 2015) - Waters, Melinda; Simon, Linda; Simons, Michele; Davids, Jennifer; Harreveld, Bobby
Abstract : Purpose: – As neoliberal reforms take hold in the vocational education and training (VET) sector in Australia, there is renewed interest in the quality of teaching practice. However, despite the value of practitioner inquiry to the quality of teaching in schools, scholarly practice in higher education, and established links between the quality of teaching and outcomes for learners and between practice-based inquiry and pedagogic innovation in VET, the practices has received little attention. The purpose of this paper is to explore the value of a college-wide culture of scholarly activity to learners, enterprises, VET institutions, educators and the national productivity agenda. Design/methodology/approach: – Drawing on the education literature, empirical examples of scholarly activity drawn from the authors' experiences of working with VET practitioners, this paper asks what constitutes research and inquiry in VET, why should these practices be integral to educative practice and what value do they bring to the sector? In addressing the questions, the authors explore how research and inquiry is defined in the literature and draw on three empirical examples of scholarly activities to provide a national, institutional and individual view. A discussion about the value of scholarly activities to VET stakeholders and how the practices might be fostered and sustained concludes the paper. Findings: – The paper concludes that practice-based scholarly activities in VET cultivate rich potential for renewed and innovative pedagogies that improve outcomes for learners, respond to industry demands for innovative skills, build "pedagogic capital" for VET institutions, enrich the knowledge base of policy makers and build resilience and professionalism. The authors conclude by positioning VET educators as scholars in their own right along a continuum of scholarly activity and posing the proposition that when valued, scholarly activities are practices for new times that will build a strong and vibrant profession for the future. Research limitations/implications: – This paper brings together the authors' experiences of working with VET practitioners as the authors engage in scholarly activities. While each vignette was drawn from a formal research project in each case, the paper itself was not structured around a formal research activity, although a small survey was undertaken for vignette 1. This poses limitations to the findings of the study. However, the purpose of the paper is not to be conclusive but to forward an argument for more scholarly activity in VET in order to promote further research and debate. Originality/value: – This paper contributes to the current debate in Australia about the quality of teaching in VET and the sectors' capability to produce "work-ready" graduates. It brings to the fore the value of scholarly activity for educators, learners, industry and communities, VET institutions and the broader national innovation agenda. As such, it has relevance to all VET stakeholders, most particularly policy makers, leaders and practitioners in VET.